2020
DOI: 10.21203/rs.3.rs-115082/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of Viremia on Organ Failure, Biomarkers and Mortality in a Swedish Cohort of Critically ill COVID-19 Patients

Abstract: BackgroundThe spread of virus via the blood stream has been suggested to contribute to extra pulmonary organ failure in Coronavirus disease 2019 (COVID-19). We assessed SARS-CoV-2 RNAemia (RNAemia) and the association between RNAemia and inflammation, organ failure and mortality in critically ill COVID-19 patients.MethodsIn a tertiary center we included all patients with PCR verified COVID-19 and consent admitted to ICU. SARS-CoV-2 RNA copies above 1000/ml measured by PCR in plasma was defined as RNAemia and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…8,10,23 Reported associations between RNAaemia and extrapulmonary involvement are more varied. 2,24,25 In addition to characterising the temporal dynamics of clinical deterioration, we included a more comprehensive scope of potential confounders than previous studies. 8 We also use cross-validation not only for model selection, but to assess the relative predictability of clinical severity (good, AUROC 0·82), extrapulmonary complications (fair, AUROC 0·73), and RNAaemia itself (poor, AUROC 0·66).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,10,23 Reported associations between RNAaemia and extrapulmonary involvement are more varied. 2,24,25 In addition to characterising the temporal dynamics of clinical deterioration, we included a more comprehensive scope of potential confounders than previous studies. 8 We also use cross-validation not only for model selection, but to assess the relative predictability of clinical severity (good, AUROC 0·82), extrapulmonary complications (fair, AUROC 0·73), and RNAaemia itself (poor, AUROC 0·66).…”
Section: Discussionmentioning
confidence: 99%
“…The association we observed between RNAaemia and EPCs (which we defined conservatively based on diagnoses at discharge, rather than surrogate biomarkers alone), is stronger than in some previous reports. 25 Extrapulmonary injury could result from direct viral toxicity, endothelial cell damage and thromboinflammation, dysregulation of the immune response, or dysregulation of the renin–angiotensin–aldosterone system. 2 Transaminitis, a common hepatobiliary complication we observed in RNAaemic patients, might result from direct hepatocellular injury by SARS-CoV-2, from cytokine storm and hypoxia-associated metabolic derangement, or from drug-induced liver injury (particularly secondary to investigational agents such as remdesivir, lopinavir, and tocilizumab).…”
Section: Discussionmentioning
confidence: 99%
“…Post-mortem studies have demonstrated viral dissemination and seeding of organs including the bone marrow, heart, and gastrointestinal tract 19 . In a Swedish cohort of critically ill COVID-19 patients, the presence of viremia was associated with the need for renal replacement therapy and poor clinical outcome 20 .…”
Section: Discussionmentioning
confidence: 99%